Unlocking the full potential of rare disease drug development: exploring the not-for-profit sector’s contributions to drug development and access - Vavassori, Stefano; Russell, Sean; Scotti, Celeste; Benvenuti, Stefano (Frontiers in Pharmacology, 2024)
This commentary provides a comprehensive overview of the challenges and opportunities in the field of drug development for rare diseases and especially of gene therapy products for ultra-rare diseases. It discusses the limited market size, reimbursement and scientific complexities that deter pharmaceutical investment in this field. Highlighting the pivotal role of charitable organizations like Fondazione Telethon, it showcases their efforts in funding research and ensuring access to innovative therapies. This commentary also addresses the challenges in therapy distribution, particularly regarding sustainability and global access. It outlines Fondazione Telethon's operational model to try to address these challenges. Finally, it appeals to governments and regulatory bodies to implement policies and incentives aimed at further fostering innovation and accessibility in rare disease drug development and access.